Historical Analysis Decline and Destruction the Dynasty Umayyah (661-770 AD) - Rozali, M. (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
This paper analyzes the history of the decline and destruction of the Umayyad Dynasty (660-770 AD). The research used in this study is a study of historical manuscripts or writings. The question in this paper is what are the factors of the decline and destruction of the Umayyad dynasty? The results of this paper are: First, the factors of the decline of the Umayyad dynasty are: a. The emergence of tribal fanaticism in Arab tribes; b. The strong influence (Arabusme) of group fanaticism that triggered social jealousy among non-Arabs (Mawali); c. The struggle for power within the extended family of the Umayyad dynasty; d. The dissolution of several rulers (caliphs) in the abundance of wealth and power. Second, the factors that brought the Umayyad dynasty to the gates of destruction: a. The absence of a standard system of government change (caliph) that can be used as a benchmark in the change of caliph; b. The strong opposition movement from the Shiites and Khawarij; c. Ethnic disputes and conflicts between Arab tribes that caused the rulers to have difficulty in establishing unity and togetherness; d. Luxurious lifestyle in the Umayyad family environment; e. The attention of the Umayyad rulers to the development of religion was very lacking; f. The emergence of a new force pioneered by the descendants of al-Abbas bin Abd. Al-Muthalib and supported by Bani Hashim, the Shiites and the Mawali.